2009
DOI: 10.1098/rspa.2009.0147
|View full text |Cite
|
Sign up to set email alerts
|

Internal resonance of vibrational modes in single-walled carbon nanotubes

Abstract: We show, by molecular dynamics simulations, that 2 : 1 internal resonance may occur between a radial breathing mode (RBM) and a circumferential flexural mode (CFM) in single-walled carbon nanotubes (SWCNTs). When the RBM vibration amplitude is greater than a critical value, automatic transformations between the RBM and CFM with approximately half RBM-frequency are observed. This discovery in the discrete SWCNT atom assembly is similar to the 2 : 1 internal resonance mechanism observed in continuum shells. A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In [9], parametric-resonance-induced mode transformation in single-walled nano-tubes, modeled as continuous elastic shells, is analyzed through a Mathieu equation and multiple instability tongues are obtained. In [10] that analysis is improved by the use of a non-local elasticity model. In [11] parametric-resonanceinduced mode-switching is analyzed on the basis of a continuum shallow shell model.…”
Section: Introductionmentioning
confidence: 99%
“…In [9], parametric-resonance-induced mode transformation in single-walled nano-tubes, modeled as continuous elastic shells, is analyzed through a Mathieu equation and multiple instability tongues are obtained. In [10] that analysis is improved by the use of a non-local elasticity model. In [11] parametric-resonanceinduced mode-switching is analyzed on the basis of a continuum shallow shell model.…”
Section: Introductionmentioning
confidence: 99%
“…This intermittent transformation between RBM and CFM may be related to the 2:1 internal resonance, which has been observed in other non-linear systems (Nayfeh and Arafat, 2006). The existence of this automated internal nonlinear resonance in SWCNTs has been further demonstrated using molecular dynamics (MD) and local and non-local continuum models (Li and Shi, 2008;Shi et al, 2009). …”
Section: Introductionmentioning
confidence: 89%
“…Recently, it has been revealed that vibration mode transformation is a common phenomenon that may happen in engineering structures at very different length scales governed by 2:1 or similar internal resonance mechanism. For example, strain growth in explosion containment vessels is related to the vibration mode transformation (Zhu et al, 1997, Duffey and Romero, 2003 and the intermittent mode transformation in single-walled carbon nanotubes was predicted in (Li and Shi, 2008, Shi et al, 2009a,2009b, Shi et al, 2009c. Since many natural, bio-and engineering structures have similar geometries to cylindrical and spherical shells, the vibration mode transformation may be realised in all these structures.…”
Section: Introductionmentioning
confidence: 99%